Gut microbiota, a new frontier to understand traditional Chinese medicines. (April 2019) - Feng, Wuwen; Ao, Hui; Peng, Cheng; Yan, Dan
Graphical abstract: Abstract: As an important component of complementary and alternative medicines, traditional Chinese medicines (TCM) are gaining more and more attentions around the world because of the powerful therapeutic effects and less side effects. However, there are still some doubts about TCM because of the questionable TCM theories and unclear biological active compounds. In recent years, gut microbiota has emerged as an important frontier to understand the development and progress of diseases. Together with this trend, an increasing number of studies have indicated that drug molecules can interact with gut microbiota after oral administration. In this context, more and more studies pertaining to TCM have paid attention to gut microbiota and have yield rich information for understanding TCM. After oral administration, TCM can interact with gut microbiota: (1) TCM can modulate the composition of gut microbiota; (2) TCM can modulate the metabolism of gut microbiota; (3) gut microbiota can transform TCM compounds. During the interactions, two types of metabolites can be produced: gut microbiota metabolites (of food and host origin) and gut microbiota transformed TCM compounds. In this review, we summarized the interactions between TCM and gut microbiota, and the pharmacological effects and features of metabolites produced during interactions between TCM and gut microbiota. Then, focusing on gut microbiota and metabolites, we summarized the aspects in which gut microbiota has facilitated our understanding of TCM. At the end of this review, the outlooks for further research of TCM and gut microbiota were also discussed.